2019
DOI: 10.3389/fcimb.2019.00088
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin D3 Deficiency Increases Resistance to Leishmania (Leishmania) amazonensis Infection in Mice

Abstract: The leishmaniases are a group of diseases caused by Leishmania parasites, which have different clinical manifestations. Leishmania (Leishmania) amazonensis is endemic in South America and causes cutaneous leishmaniasis (CL), which can evolve into a diffuse form, characterized by an anergic immune response. Since the leishmaniases mainly affect poor populations, it is important to understand the involvement of immunonutrition, how the immune system is modulated by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This differential effect of the infectious dose on the evolution of the disease was not observed in other vaccine models such as C57BL/6 mice inoculated with a total protein-based vaccine LaAg [45]. On the other hand, the influence of the L. amazonensis inoculum size in the progression of the disease was previously reported for different murine models [6] and also influenced the studies regarding the effects of immunonutrition in the outcome of infection in BALB/c and C57BL/6 mice [46]. In the same direction, the protective effect of a vaccine based on the intranasal administration of extracellular serine proteases is inversely proportional to the infectivity of the inoculum [13].…”
Section: Discussionmentioning
confidence: 93%
“…This differential effect of the infectious dose on the evolution of the disease was not observed in other vaccine models such as C57BL/6 mice inoculated with a total protein-based vaccine LaAg [45]. On the other hand, the influence of the L. amazonensis inoculum size in the progression of the disease was previously reported for different murine models [6] and also influenced the studies regarding the effects of immunonutrition in the outcome of infection in BALB/c and C57BL/6 mice [46]. In the same direction, the protective effect of a vaccine based on the intranasal administration of extracellular serine proteases is inversely proportional to the infectivity of the inoculum [13].…”
Section: Discussionmentioning
confidence: 93%
“…In agreement with this study, L. mexicana -infected mice treated with vitamin D exhibit a reduction in lesion size (Ramos-Martínez et al ., 2013). In contrast, L. amazonensis- infected mice that received a vitamin D-deficient diet controlled the lesion development better than mice that received a regular diet (Bezerra et al ., 2019). In addition, C57BL/6 mice deficient for the VDR and infected with L. major developed significantly smaller lesions and had a reduced inflammatory process when compared to C57BL/6 WT mice (Whitcomb et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All these effects promoted by vitamin D in the immune system are unfavourable to the development of an effective immune response against Leishmania spp., which thus favours the parasite growth and the consequent disease progression in the host. Our previous data have demonstrated that in the absence of vitamin D in the diet, there is a decrease in the lesion size of infected mice due to an increase of Th1 cells (Bezerra et al ., 2019). However, in this paper, we have investigated the vitamin D role at the host cell level, and we suggest that vitamin D (D 2 and D 3 ) can directly cause a slight increase in the control of the parasite load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some observational, preclinical, and clinical studies have shown that low levels of VitD increase the risk of developing multiple diseases in humans (cancer, diabetes, autoimmune diseases and infectious diseases such as toxoplasmosis, AIDS, influenza or malaria) [ 26 32 ]. However, few studies have investigated VitD and leishmaniasis, with contradictory results depending on the animal model and Leishmania species [ 33 36 ]. We previously showed, for the first time, that dogs with clinical leishmaniasis and also those with asymptomatic infection presented lower VitD serum concentration than non-infected dogs.…”
Section: Introductionmentioning
confidence: 99%